Regulation of Metastasis by microRNAs in Ovarian Cancer - Wang, Yongchao; Kim, Sangmi; Kim, Il-man (Frontiers in Oncology, 2014)
Ovarian cancer (OC) is the second most common and the most fatal gynecologic cancer in the United States. Over the last decade, various targeted therapeutics have been introduced but there has been no corresponding improvement in patient survival mainly because of the lack of effective early detection methods. MicroRNAs (miRs) are small, non-coding RNAs that regulate gene expression post-transcriptionally. Accumulating data suggest central regulatory roles of miRs in modulating OC initiation, progression and metastasis. More recently, aberrant miR expression has been also associated with cancer stem cell (CSC) phenotypes and development of CSC chemo-resistance. Here, we review recent advances on miRs and OC metastasis and discuss the concept that miRs are involved in both CSC transformation and subsequent OC metastasis. Finally, we describe the prevalence of circulating miRs and assess their potential utilities as biomarkers for OC diagnosis, prognosis, and therapeutics.